PREVALENCE OF HYPERENSION IN YOUNGER POPULATION ACCORDING TO NEW ACC GUIDELINES 2017 - Afreen, Aneela; Khan, Muhammad Nadir; Nousheen, Rukhshanda; Shehzad, Syed Khurram; Rehman, Atiq Ur; Rana, Faraz Saeed (Pakistan Armed Forces Medical Journal, 2019)
Objective: To estimate the prevalence of hypertension in our younger population according to new guidelines released by American College of Cardiology in 2017. Study Design: Descriptive cross sectional study. Place and Duration of Study: Army Cardiac Centre Lahore, from Feb 2019 to Apr 2019. Methodology: One hundred and ninety seven people were enrolled in the study as per inclusive criteria. Two blood pressure measurements were taken 5 minutes apart using proper technique as described in ACC/AHA guidelines and then average blood pressure of the recorded readings was used to calculate the results. Results: Out of 197 patients enrolled in the study, 103 (52.28%) were females and 94 (47.71%) were males. Age varied from 18 to 60 years with a mean age of 30.87 ± 5.76. Maximum number of individuals i.e. 109 (55.32%) were within 21-30 years. Out of 197, 105 (53.3%) were having normal blood pressure i.e. <120/<80 mmHG, 23 (11.67%) were having elevated systolic blood pressure i.e. 120-129/<80 mmHG, 53 (26.9%) were having blood pressure measurement in range of stage 1 hypertension i.e. systolic blood pressure between 130-139mmHg or diastolic blood pressure between 80-89 mmHG while 16 (8.12%) were having blood pressure in range of stage 2 hypertension i.e. systolic blood pressure >140mmHG or diastolic blood pressure >90 mmHG. Conclusion: Our findings highlighted the prevalence of silent hypertension in apparently normal individuals and the necessity to overcome this increasing disease burden.